Citizens' Awareness and Dissemination of Local Government Unit (LGU) Processes in General Santos City - Barangai, Omairah (Journal of Interdisciplinary Perspectives, 2024)
This study examined citizen awareness of Local Government Unit (LGU) processes and their dissemination in General Santos City. The primary objectives are to identify gaps in awareness, uncover dissemination challenges, and propose improvement recommendations. A descriptive correlational research design was used, with quantitative data gathered from 390 randomly selected respondents across 26 barangays. Structured questionnaires measured awareness on a 5-point Likert scale and dissemination on a 4-point Likert scale. Findings indicate high awareness of basic services and facilities, land management, and revenue generation. Dissemination effectiveness was rated moderately high. The study found significant positive correlations between dissemination extent and citizen awareness, with strong correlations for basic services and moderate correlations for land reclassification and revenue generation. These positive correlations suggest a promising potential for improvement. The study concludes that improving the dissemination of LGU processes is crucial for fostering informed, engaged communities. Recommendations include targeted, community-specific, and technology-driven communication strategies to enhance transparency, accountability, and citizen participation in local governance. These improvements are essential for more effective and responsive governance in General Santos City. The implications of this study suggest that enhancing dissemination practices can lead to better-informed citizens, promoting greater civic engagement and trust in local government.